Fluid balance of adolescent swimmers during training - Adams, J. D.; Kavouras, S. A.; Robillard, J. I.; Bardis, C. N.; Johnson, E. C.; Ganio, M. S.; McDermott, B. P.; White, M. A. (The Journal of Strength and Conditioning Research, 2016)
Swimming, either competitively or leisurely, is a unique activity that involves prolonged exercise while immersed in stable water temperatures. This environment could have an influence on the hydration status of swimmers independently of fluid balance. Forty-six healthy adolescent swimmers (26 males and 20 females; 12.8 ± 2.3 years; 50.6 ± 13.4 kg) were studied during a typical training session in an indoor swimming pool. First morning, prepractice and postpractice urine samples were tested for osmolality and specific gravity, whereas all athletes consumed fluids ad libitum. Sixty-seven percent of the athletes were hypohydrated (urine osmolality [Uosm] =700 mmol·kg-1) based on their first morning urine sample, which increased to 78% immediately before training. During the 2-hour swimming practice, the minimal sweat loss (0.39 ± 0.27 L) combined with ad libitum fluid availability resulted in unchanged body weight (0.1 ± 0.3 kg). Additionally, thirst was similar (before practice: 46 ± 26, after practice: 55 ± 33 mm on a 100-mm visual analog scale) at pretraining and posttraining time points (p > 0.05). Interestingly, postpractice Uosm was reduced significantly compared with the prepractice value (630 vs. 828 mmol·kg-1; p = 0.001), without any significant change in body weight (0.1 ± 0.3 kg; p > 0.05). In conclusion, the present data indicated that more than two-thirds of the young swimmers appeared in their practice suboptimally hydrated. Although no changes in body mass were observed during the swimming practice, the decrease in urine hydration markers after swimming might less accurately reflect hydration state.